1982
DOI: 10.1016/0009-2614(82)83678-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantum yield for NO3 production from photolysis of ClONO2

Abstract: Chlorine nitrate, ClONo 2 , was photolyzed at 249 nm by a 10 ns pulse from an excimer laser, and the primary product No 3 was followed by tunable dye-laser absorption at 662 nm. Wfth Ar or Ar plus CH 4 as carrier gases between 20 and 100 Torr, the primary quantum yield for N0 3 was 0.55 (-0.1 to+ 0.3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…These results are in excellent agreement with two other studies of the chlorine nitrate branching ratios. 5,8 For photolysis in the unfiltered quartz cell (λ > 200 nm), the relative branching ratios are 0.61 ( 0.20 for the ClO + NO 2 channel and 0.31 ( 0.20 for the Cl + NO 3 channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in excellent agreement with two other studies of the chlorine nitrate branching ratios. 5,8 For photolysis in the unfiltered quartz cell (λ > 200 nm), the relative branching ratios are 0.61 ( 0.20 for the ClO + NO 2 channel and 0.31 ( 0.20 for the Cl + NO 3 channel.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have examined the branching ratios among the various dissociation pathways. [1][2][3][4][5][6][7][8][9] In 1983, Margitan reported that branching among the possible product channels was dominated by reaction 1b, with 90% of dissociation occurring via this process and the remaining 10% proceeding via reaction 1c at 266 and 355 nm. 6 He saw no evidence of the ClO product from reaction 1a even though dissociation via this channel cleaves the weakest bond in the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…CIONO2 was prepared by reacting N2Os with C12 O, according to the method of Schmeisser (1967), followed by purification as described by Marinelli and Johnston (1982). The purity of the C1ONO2 was checked by FT-IR measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Polyphyletic (A and B) and mphyletic (C and D) hypotheses of arthropod relationships. Polyphyletic hypotheses propose either that (A) onychophorans are more closely related to certain annelids than to arthropods (2) or (8) arthropodization has occurred independently at least three times (3). Hypotheses of arthropod monophyfy Propose onychophorans are either (C) primitive (4) or (D) closely allied to myriapods and hexapods (5).…”
Section: Chophorans Maximum Parsimony Analyses and Monophyly Testingmentioning
confidence: 99%